Silver nitrate concentration on silver nanoparticles formation attached on cellulose nanocrystal matrix - Norlin, Pauzi; Segaran, Sivenesh Chandra; Shahril, Mohamad; Saidatul Shima, Jamari (Elsevier Ltd, 2023)
Cellulose nanocrystals (CNCs) with silver nanoparticle composites are used in various applications, ranging from packaging to biomedical. Therefore, the optimum performance of this hybrid nanomaterial can be achieved by controlling agglomeration in the silver nanoparticle synthesis. The agglomeration behaviour can be monitored by integrating CNCs as polymer matrix during the synthesis. This work aimed to investigate the effect of silver nanoparticles (AgNPs) synthesised from different silver precursor concentrations and loaded on the surface of CNCs. The cellulose nanocrystal was isolated from an oil palm empty fruit bunch (EFB). The AgNPs were synthesised by using the reduction technique of silver nitrate at 0.1 M and 0.5 M concentrations and with the aid of glucose solution. The AgNPs_CNC nanosuspension was analysed by using UV–Vis spectroscopy, FTIR, DSC, and FESEM/EDX. The spectroscopy data from UV–Vis indicated a strong absorption peak at 385 nm due to the formation of the nanoparticles in AgNPs_CNC_0.5 nanosuspension. Meanwhile, the morphological result showed that the AgNPs formed were spherical in shape (57.8 nm) with strong existence of silver, carbon, and oxygen. Therefore, the AgNPs_CNC nanosuspension was successfully synthesised by using 0.5 M silver nitrate with uniform and well-distributed nanoparticles.